LEGAL POLITICS OF EASING THE ADMISSION OF FOREIGN WORKERS UNDER LAW NO. 11/2020 ON JOB CREATION - Pardosi, Gabriel Tryogi Rahmadi; Jamil (jfpublisher, 2023)
The Indonesian government drafted a law on job creation using the omnibus law method and is effective on November 2, 2020, which aims to regulate job creation attempts that are expected to accommodate Indonesian workers in the midst of competitive competition. There is a statement that the Omnibus law was approved to allow foreign workers into Indonesia freely, which is incorrect statement. In fact, in Article 89 regarding the amendment to Article 42 Paragraph 1 of Law No. 13/2003, there are requirements for hiring foreign workers in Indonesia. The article states that every employer who employs foreign workers must have an endorsement of the plan for the use of foreign workers from the central government. Therefore, this research aims to find out the legal politics of easing the admission of foreign workers after the issuance of the Law on job creation and legal protection of Indonesian workers after the issuance of the Law. This research is descriptive normative research which used legal doctrines, legal issues and legal principles related to the research topic. There are several results from the research, such as (1) the existence of regulations that regulate the easing of foreign workers after the issuance of Law No. 11/2020 on job creation, which consists of Articles 42, 44, 46; (2) the existence of legal politics in the easing of foreign workers in Indonesia, by prioritizing the interests of companies in using foreign workers; (3) prioritizing the rights of local workers in getting jobs easily.